Key to sessile gnesiotrochan rotifers: Floscularia (Monogononta; Flosculariidae) - Lafleur, Alexandre; Davies, Natalie; Hochberg, Rick; Walsh, Elizabeth J.; Wallace, Robert L. (Zootaxa, 2024)
Correct identification of species is necessary if we are to understand their biology, ecology, and evolutionary history, as well as to catalog their global biodiversity. This is acutely critical for many micrometazoans like rotifers, which are often difficult to identify because of their small size and complicated morphologies. Rotifers are ubiquitous micrometazoans that are found worldwide in fresh, brackish, and some marine waters. However, their study is hindered by a lack of both taxonomic expertise and concomitantly adequate guides to the identification of some taxa. These deficiencies are particularly true for the sessile species. To help alleviate these impediments, we assembled information from the literature on easily recognizable characters of all nine valid species in one notable genus: Floscularia (Monogononta; Gnesiotrocha; Flosculariidae). Using that information we developed a simple, dichotomous key to enable workers to identify species in this genus. Our key emphasizes easily observable characters of adult female morphology, including features of their tubes, anterior ends, trophi, and colony formation abilities, thereby allowing for relatively quick identification.